The Oxford handbook of modern African history - Parker, John, 1960-; Reid, Richard J. (Richard James) (New York : Oxford University Press, 2013)
"This collection of essays ... will allow readers to explore various aspects ... of the continent's history over the last two hundred years ."--Book jacket.
Introduction : African histories : past, present, and future / Richa rd Reid and John Parker -- Key themes in African history. Ecology and e nvironment / James McCann ; Demography and disease / Shane Doyle ; Afri can slave trades in global perspective / Pier M. Larson ; States and st atelessness / Walter Hawthorne ; Ethnicity and identity / Richard Walle r ; Warfare and the military / Richard Reid ; The African diaspora / Jo hn Parker -- The colonial encounter. African colonial states / Heather J. Sharkey ; Law, crime, and punishment in colonial Africa / Richard Ro berts ; Work and migration / Emily Lynn Osborn ; Chieftaincy / Justin W illis ; Between the present and history : African nationalism and decol onization / Jean Allman -- Religion and belief. Islam / Marie Miran-Guy on and Jean-Louis Triaud ; Christianity / David Maxwell ; Indigenous Af rican religions / Robert M. Baum ; New religious movements / Sean Hanre tta -- Society and economy. Education and literacy / Carol Summers ; Wo men and gender / Barbara M. Cooper ; Urbanization and urban cultures / John Parker ; Health and healing / Nancy Rose Hunt ; Youth / Nicolas A rgenti and Deborah Durham ; Economic growth / Morten Jerven -- Arts and the media. Visual cultures / Sidney Littlefield Kasfir ; Music in mode rn African history / Viet Erlmann ; African literary histories and hist ory in African literatures / Stephanie Newell ; Communications and medi a in African history / James R. Brennan.
Includes bibliographical references and index.
Keywords: Africa -- History -- 1801-1884.; Africa -- History -- 1884-1945.; Africa -- History -- 1945-1960.